Comparison service quality of annual motor vehicle tax payment at SAMSAT Nganjuk Regency - Mansyur Setiawan; Tree Setiawan Pamungkas; Sutomo Sutomo (Junal Ilmu Manajemen, 2023)
This study aims to examine the differences in the quality of annual motor vehicle tax payment services at SAMSAT Featured Morning and SAMSAT Corner Nganjuk Public Service Mall. The sample in this study amounted to 200 people with each form of service taken 100 respondents using incidental sampling technique. Data analysis using Mann Whitney non-parametric statistical test with the help of SPSS 25 for windows programme. The results of this study indicate that there is a significant difference in the quality of annual motor vehicle tax payment services between SAMSAT Featured Morning and SAMSAT Corner Nganjuk Public Service Mall with a significance value of 0.000 smaller than 0.05. The tendency of service quality is better at SAMSAT Corner Nganjuk Public Service Mall with a mean value of 126.56 compared to SAMSAT Featured Morning of 74.45.